PLANTING THE SEED: THE IMPACT OF AN EARLY ENTREPRENEURSHIP EDUCATION PROGRAM ON INNOVATION MINDSETS IN PRIMARY SCHOOL CHILDREN - Latu, Tuiasosopo; Sualau, Vaele; Pio, Maile (International Journal of Educatio Elementaria and Psychologia, 2025)
Early entrepreneurship education has the potential to foster innovation and critical thinking skills in children. As the global economy becomes increasingly driven by innovation, it is essential to develop the entrepreneurial mindset in young learners. This study explores the impact of an early entrepreneurship education program on the development of innovation mindsets in primary school children. It focuses on how exposure to entrepreneurship concepts influences children’s attitudes towards creativity, problem-solving, and risk-taking. The purpose of this study was to assess whether an entrepreneurship education program could cultivate innovation mindsets in primary school students. A mixed-methods approach was used, combining pre- and post-program surveys with qualitative interviews and classroom observations. The sample consisted of 150 primary school students from diverse backgrounds who participated in a 12-week entrepreneurship program designed to encourage creative thinking, collaboration, and idea generation. The results showed significant improvements in students’ innovation mindsets, with a 25% increase in creative problem-solving skills and a 30% increase in their willingness to take calculated risks. Additionally, qualitative data revealed a positive shift in students’ attitudes towards entrepreneurship, with many expressing interest in starting their own businesses in the future. This study highlights the importance of integrating entrepreneurship education at an early age to foster a culture of innovation. It suggests that such programs can play a vital role in shaping future generations’ ability to adapt and thrive in a rapidly changing world.